2011
DOI: 10.5021/ad.2011.23.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiologic Survey of Varicella-Zoster Virus in Korean Adults Using Glycoprotein Enzyme Immuno Assay and Fluorescent Antibody to Membrane Antigen Test

Abstract: Most (90.2%) Korean adults ≥40-years-of-age have a protective level of gpEIA antibody against varicella and 98.6% were FAMA seropositive. The GMT of gpEIA antibody was significantly increased with age, and was higher in adults with a history of HZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Choi et al (8) reported the seroprevalence in subjects < 1 yr of age to over 75 yr of age and the results were similar to our study. Another study was performed in subjects over 40 yr of age using fluorescent antibody to membrane antigen test (FAMA) and the results showed seropositivity of 98.6% in that age group (9). According to age groups, our results showed seroprevalence of 67.3% in subjects as early as 1-4 yr of age.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (8) reported the seroprevalence in subjects < 1 yr of age to over 75 yr of age and the results were similar to our study. Another study was performed in subjects over 40 yr of age using fluorescent antibody to membrane antigen test (FAMA) and the results showed seropositivity of 98.6% in that age group (9). According to age groups, our results showed seroprevalence of 67.3% in subjects as early as 1-4 yr of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, unfixed cells cannot be stored for a long time, therefore, some laboratories used glutaraldehyde for cell fixing 31-33. Besides fixation methods, cell lines, VZV strains, reference sera, and cutoff values are different between laboratories 3,20,24,30,31,33-35. Williams, et al3 used a wild type VZV Ellen strain, and recently the Oka vaccine strain has been used in some laboratories 3,30,33,35.…”
Section: Resultsmentioning
confidence: 99%
“…MGLu cells were cultured and infected with Varilrix™ (GSK, UK) as described previously 30. When 60-70% of the cells showed a cytopathic effect, cells were harvested and used as a FAMA antigen 30. The FAMA test was performed according to William's method with some modification 3,30.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, researchers around the world have screened protective antigens of varicella zoster virus (VZV), exploring a series of antigen markers with various degrees of immune protective effects (1). Previous studies have demonstrated that the glycoprotein E (gE) antigen is one of the most promising candidate antigen markers (2,3). gE is one of the most important protective antigens in VZV, and since it is capable of inducing cellular and humoral immunity, gE is considered the most appropriate candidate antigen for a DNA vaccine (4).…”
Section: Introductionmentioning
confidence: 99%